Purchasing Supporting System Amaris Hotel Mampang - Nugraha, Rizki Nurul; Choerunisa, Siti; Ramadhani, Fahira; Ramadhannu, Syaldisa; Shendy, Muhammad Ilham (Jurnal Ilmiah Wahana Pendidikan, 2023)
Hotel is a service that offers to tourists, hotel management must have strategies and innovations to survive in the midst of competition. One way to win the competition is to improve the existing hotel procurement system to be more efficient. All hotel facility needs run because of purchasing. In this study the authors used descriptive qualitative research methods. The data collection technique used by the author is primary data where the data is collected through interviews. In the operational process of purchasing goods at Amaris Hotel Mampang, there is one special department, namely the accounting department. The procurement of goods needed by Amaris Hotel Mampang is carried out by the purchasing department in charge of making purchases or orders to the supplier (vendor) according to the goods/products needed. Based on the results of research on the "Purchasing Supporting System Amaris Hotel Mampang", it can be concluded that the procurement process at Amaris Hotel Mampang, in the purchasing, receiving, and store keeper sections uses data collection with the forms listed in order to facilitate the recording process.